Office 2013 elearning kit for dummies - Wempen, Faithe. (John Wiley and Sons, 2014)
Discover the power ò microsoft office 2013 and take your productivity to the next level with ofice 2013 for dummnies . Whether building documents in world, crunching numbers in excel, staying in touch with outlook, or producing great presentations with powerpoint, this is your guide for getting to work with office 2013